The Concept of Jihad in Islam: An Historical Perspective - Sulaiman, Kamaldeen Olawale (ASPENSI in Bandung, Indonesia, 2015)
ABSTRACT: Islam, the youngest of the three Semitic religions in the world today, is the fastest growing religion on earth. As a result, it faces a lot of criticism and blackmail directed at its adherents as well as renowned Muslims. The Islamic view on âshariahâ (divine law), âhijabâ (headscarf), polygamy, and, above all, âjihadâ, are erroneously and mischievously translated by some non-Muslims historians. âJihadâ to them is nothing but war, terrorism, assassination, and using the swordâs edge to convert non-Muslims to Islam. This paper intends to analyze the historical perspectives of âjihadâ, the concept, justifications, and the methods of recruitment of soldiers in âjihadâ. It also analyses the Islamic instructions for Muslims in war front and the treatment of Islamic prisoners of war. The method of approach is purely from written sources, which comprise of documents, monographs, manuscripts, books, journals as well as magazines. The study reveals that those wars fought by the Muslims were for their own protection and that of the faith. Likewise, the issue of forceful conversion to Islam, either by the edge of the sword or barrel of a gun, as often ranted by some non-Muslim historians, holds no ground in Islam. The paper, therefore, recommended that one should look into the early history of Islam and see that it was the Muslims that were cheated, humiliated, banished, and their properties were confiscated. The paper concluded that the assertion of some non-Muslims that Islam spread through violence, and people were forced to either accept Islam or die by sword is not only untrue but also baseless.KEY WORDS: Islam, concept of âjihadâ, faith, Islamic instruction, non-Muslims historian, fundamentalists, conversion, terrorism, and misperceptions on Islam.About the Author: Kamaldeen Olawale Sulaiman, Ph.D. is a Lecturer at the Department of Religious Studies ESU (Ekiti State University) in Ado-Ekiti, Nigeria. For academic interests, the author is able to be contacted via phone at: +2348068298472 or via e-mail at: drsulaimanko@yahoo.comHow to cite this article? Sulaiman, Kamaldeen Olawale. (2015). âThe Concept of Jihad in Islam: An Historical Perspectiveâ in TAWARIKH: International Journal for Historical Studies, Vol.7(1) October, pp.111-120. Bandung, Indonesia: Minda Masagi Press, ISSN 2085-0980.Chronicle of the article: Accepted (February 23, 2015); Revised (June 1, 2015); and Published (October 28, 2015).